Real-World Six-Year National Cost-Minimization Analysis of IncobotulinumtoxinA and OnabotulinumtoxinA in the VA/DoD Healthcare Systems - Kazerooni R; Howard IM; Keener AM; Bounthavong M (Dove Medical Press, 2021)
Rashid Kazerooni, 1 Ileana M Howard, 2, 3 Adrienne M Keener, 4, 5 Mark Bounthavong 6, 7 1Merz Pharmaceuticals, LLC, Raleigh, NC, 27615, USA; 2Rehabilitation Care Services, VA Puget Sound, Seattle, WA, USA; 3Department of Rehabilitation Medicine, University of Washington, Seattle, WA, USA; 4Department of Neurology, David Geffen School of Medicine, Los Angeles, CA, USA; 5Parkinson's Disease Research, Education, and Clinical Center, Greater Los Angeles Veterans Affairs Medical Center, Los Angeles, CA, USA; 6VA Health Economics Resource Center, VA Palo Alto Health Care System, Menlo Park, CA, USA; 7Department of Clinical Pharmacy, UCSD Skaggs School of Pharmacy & Pharmaceutical Sciences, SanDiego, CA, USACorrespondence: Rashid KazerooniAssociate Director, Health Economics and Outcomes Research, Merz Pharmaceuticals, LLC, 6601 Six Forks Road, Suite 430, Raleigh, NC, 27615, USATel +1.785.249.3233Email rashid.kazerooni@merz.comPurpose: This study sought to perform a real-world, long-term cost-minimization analysis for incobotulinumtoxinA (Xeomin®) versus onabotulinumtoxinA (Botox®), given the established non-inferiority when utilized at similar doses.Methods: The Department of Veterans Affairs (VA) and Department of Defense (DoD) national healthcare systems were included in this analysis. Real-world purchase data for incobotulinumtoxinA were used to estimate the direct drug costs between calendar years 2014 and 2019. Publicly available federal pharmaceutical prices (Federal Supply Schedule and Big 4) were used. The primary outcome was the difference in total direct costs nationally for incobotulinumtoxinA (real-world) versus having hypothetically utilized onabotulinumtoxinA (projected) for similar utilization. Sites utilizing ≥ 100 vials (of 100 Unit equivalents) of incobotulinumtoxinA annually were categorized as “major adopters”. IncobotulinumtoxinA 50 Unit vials were assumed to be an alternative to a 100 Unit vial of onabotulinumtoxinA for 50% of such vial purchases in the base case scenario to account for differences in wastage.Results: Over the six-year study time frame, 156 sites (76.8%) utilized incobotulinumtoxinA of the 203 total VA healthcare systems and DoD medical centers. Of these sites, 67 were major adopters for at least one year, with a mean of 3.4 years spent as a major adopter over the study period. Average annual savings per major adopter was $105,782. IncobotulinumtoxinA costs for all VA/DoD sites was $46.39 million for the six-year period versus a projected $71.92 million onabotulinumtoxinA cost—a total savings of $25.53 million (35.5% relative reduction). Approximately, 82.8% of savings stemmed from lower drug acquisition cost ($21.14 million) and 17.2% of savings ($4.39 million) was related to reduced wastage. It was estimated that a total of 9958 extra onabotulinumtoxinA 100 Unit vials would have been wasted during the six-year period, translating to the need for a 5.9% increase in vial purchases versus incobotulinumtoxinA.Conclusion: Meaningful cost savings were realized related to incobotulinumtoxinA adoption over a long-term time frame in the VA/DoD healthcare systems.Keywords: Xeomin, Botox, cost, federal, savings